2007
DOI: 10.1111/j.1442-2042.2007.01839.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological review of 46 primary retroperitoneal tumors

Abstract: Objectives:To clarify the clinical factors including diagnostic imaging findings that may correlate with the histopathological malignancy in primary retroperitoneal tumors. Methods:The clinical backgrounds and imaging findings of 22 benign and 24 malignant primary retroperitoneal tumors were retrospectively investigated , and the prognosis of patients with malignant retroperitoneal tumors was assessed. Results: There were significant correlations between the presence of symptoms and malignancy (P < 0.01), as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 11 publications
0
33
0
Order By: Relevance
“…The cysts are lined by a pseudostratified ciliated columnar epithelium, in addition to bronchial glands, smooth muscle cells or cartilage (3,5). Bronchogenic cysts commonly occur in the mediastinal region of the thorax, and are occasionally located in subcutaneous tissue, the pericardium, the spinal canal and other areas of the body (1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cysts are lined by a pseudostratified ciliated columnar epithelium, in addition to bronchial glands, smooth muscle cells or cartilage (3,5). Bronchogenic cysts commonly occur in the mediastinal region of the thorax, and are occasionally located in subcutaneous tissue, the pericardium, the spinal canal and other areas of the body (1).…”
Section: Discussionmentioning
confidence: 99%
“…However, with the development of radiological techniques, the number of incidental discoveries of asymptomatic RBC is rapidly increasing (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the symptom of renal colic was increasing, it was speculated that there was a high possibility of renal involvement. It is known that the most effective treatment is surgical removal of the tumors, with the exception of chemosensitive tumors, and that a definitive diagnosis can usually be made from the surgical specimens (12). Thus, considering the patient's wishes, surgery was performed.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of MRI is a limitation in our diagnostic process. In the study of Tambo et al (12), a clinicopathological review of 46 primary retroperitoneal tumors identified that MRI imaging diagnosis prior to surgery was compatible with the histological diagnosis in only 26 patients (57%), and all six malignant lymphoma patients underwent biopsy or surgical resection. Therefore, if clinical diagnosis cannot be determined by MRI, definitive histological diagnosis by biopsy or tumor resection is required in order to determine the appropriate treatment.…”
Section: Discussionmentioning
confidence: 99%